A model of health promotion with emphasis on physical activity for university students (2003)
Objective: The project was designed towards a model of health promotion based upon physical activity and directed to the students of the National University of Colombia. Methods: A three phase multilevel analysis method was employed. Both the disease and the population problems presented by the students were examined and documented, and the information on both of these problems was integrated. In second place, the previous experiences were identified and finally the axes and strategies of the model were established. Results: A model was defined whose main components are the networks of participation and support to the promotion of health and physical activity, the political and regulatory support and transformation, and the academic reorientation towards an integral formation and its strategies. Conclusions: The project reassured a methodology for designing health models, as well as it favored the integration, from a practical perspective, of the strategies and approaches of health promotion applied to physical activity.